2014
DOI: 10.17511/ijphr.2014.i1.05
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to assess knowledge, attitude and practice for Hepatitis B vaccination among Nurses of Government and Private Hospital of Central India

Abstract: Background: Hepatitis B is a global public health problem. In India the carrier rate of hepatitis B is higher among health care personnel. Nurses are probably the most commonly exposed health care staff exposed to needle prick, injuries and contact with infectious fluids. Objective: To assess the levels of awareness regarding infectivity of hepatitis B among nurses, their attitude towards hepatitis B vaccination and practices followed after needle stick injury. Methodology: A cross sectional observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In a similar study conducted on healthcare workers, it was found that most of the participants believed that hepatitis B can be transmitted from mother to child, unprotected sex, needle stick injury and blood transfusion. 7,8 The current study showed that 79.30% nurses and lab technicians whereas only 20.76% MPWs believed that the risk of hepatitis B leading to liver disease or liver cancer was high. In this study 98% of the nurses and lab technicians were of the opinion that hepatitis B virus infection can be prevented, whereas only 71.1% of the multipurpose workers believed the same.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a similar study conducted on healthcare workers, it was found that most of the participants believed that hepatitis B can be transmitted from mother to child, unprotected sex, needle stick injury and blood transfusion. 7,8 The current study showed that 79.30% nurses and lab technicians whereas only 20.76% MPWs believed that the risk of hepatitis B leading to liver disease or liver cancer was high. In this study 98% of the nurses and lab technicians were of the opinion that hepatitis B virus infection can be prevented, whereas only 71.1% of the multipurpose workers believed the same.…”
Section: Discussionmentioning
confidence: 63%
“…In similar studies it was found that majority of the participants were aware of the infection. 6,7 The results of our study showed that only 30.19% of the MPWs correctly knew all the modes of transmission of Hepatitis B, whereas 73.83% of the nurses and lab technicians were aware of all the correct modes. In a similar study conducted on healthcare workers, it was found that most of the participants believed that hepatitis B can be transmitted from mother to child, unprotected sex, needle stick injury and blood transfusion.…”
Section: Discussionmentioning
confidence: 70%
“…Nutrition warrants special attention during pregnancy and lactation as foetus as well as infant needs high nutrients. [1][2][3][4][5][6][7] Poor maternal diet affects mother's health, which thereafter poses a potential risk of maternal and child death. 5 However, it is important for the mother to maintain a healthy nutritional status during the time of pregnancy and lactations as it affects her own health, her ability to give birth and breastfeed a healthy infant.…”
Section: Introductionmentioning
confidence: 99%